THE FAIRY TALES OF CHILDHOOD: REFLECTIONS IN BRIEF (Fiep Bulletin - online, 2013)
This paper aims to present a brief reflection on the influence of fairy tales in children's lives, addressing comprehensively the importance in child development. It is a theoretical work on the fairy tale and its principal authors, in a qualitative way, encourages reflection and analysis about the theories and hypotheses. Some questions guided the interest in the topic, such as: what are the possible origins of fairy tales? What the child learns to experience the fairy tales? Fairy tales in their oral tradition, emerged thousands of years ago, with difficult historical accuracy. It is understood positively that they have a narrative structure, by a succession of facts and events organized in a coherent and meaningful. Finally, it is understood that fairy tales do awaken in children the joy of reading and writing, stimulating creativity, imagination and overcome their problems.
Keywords: Fairytales; Child Development; Child